Fetal cerebral Doppler changes and outcome in late preterm fetal growth restriction: prospective cohort study. (1st August 2020) - Stampalija, T.; Thornton, J.; Marlow, N.; Napolitano, R.; Bhide, A.; Pickles, T.; Bilardo, C. M.; Gordijn, S. J.; Gyselaers, W.; Valensise, H.; Hecher, K.; Sande, R. K.; et al.
ABSTRACT: Objectives: To explore the association between fetal umbilical and middle cerebral artery (MCA) Doppler abnormalities and outcome in late preterm pregnancies at risk of fetal growth restriction. Methods: This was a prospective cohort study of singleton pregnancies at risk of fetal growth restriction at 32 + 0 to 36 + 6 weeks of gestation, enrolled in 33 European centers between 2017 and 2018, in which umbilical and fetal MCA Doppler velocimetry was performed. Pregnancies were considered at risk of fetal growth restriction if they had estimated fetal weight and/or abdominal circumference (AC) < 10 th percentile, abnormal arterial Doppler and/or a fall in AC growth velocity of more than 40 percentile points from the 20‐week scan. Composite adverse outcome comprised both immediate adverse birth outcome and major neonatal morbidity. Using a range of cut‐off values, the association of MCA pulsatility index and umbilicocerebral ratio (UCR) with composite adverse outcome was explored. Results: The study population comprised 856 women. There were two (0.2%) intrauterine deaths. Median gestational age at delivery was 38 (interquartile range (IQR), 37–39) weeks and birth weight was 2478 (IQR, 2140–2790) g. Compared with infants with normal outcome, those with composite adverse outcome ( n  = 93; 11%) were delivered at an earlier gestational age (36 vs 38 weeks) and had a lower birth weight (1900 vs 2540 g). The first Doppler observation of MCA pulsatility index < 5 th percentile and UCR Z ‐score above gestational‐age‐specific thresholds (1.5 at 32–33 weeks and 1.0 at 34–36 weeks) had the highest relative risks (RR) for composite adverse outcome (RR 2.2 (95% CI, 1.5–3.2) and RR 2.0 (95% CI, 1.4–3.0), respectively). After adjustment for confounders, the association between UCR Z ‐score and composite adverse outcome remained significant, although gestational age at delivery and birth‐weight Z ‐score had a stronger association. Conclusion: In this prospective multicenter study, signs of cerebral blood flow redistribution were found to be associated with adverse outcome in late preterm singleton pregnancies at risk of fetal growth restriction. Whether cerebral redistribution is a marker describing the severity of fetal growth restriction or an independent risk factor for adverse outcome remains unclear, and whether it is useful for clinical management can be answered only in a randomized trial. © 2020 The Authors. Ultrasound in Obstetrics & Gynecology published by John Wiley & Sons Ltd on behalf of the International Society of Ultrasound in Obstetrics and Gynecology.